2010
DOI: 10.1021/ef1002974
|View full text |Cite
|
Sign up to set email alerts
|

Total Acid Number Determination in Residues of Crude Oil Distillation Using ATR-FTIR and Variable Selection by Chemometric Methods

Abstract: The total acid number (TAN) was determined in the atmospheric residue (AR) and vacuum residue (VR) of the petroleum distillation process using mid-infrared spectroscopy with attenuated total reflection in association with chemometric methods. Calibration and prediction sets consisted of 44 and 13 samples, respectively (16 AR samples and 41 VR samples). Calibration models were developed using three variableselection models: interval partial least squares (iPLS), synergy interval partial least squares (siPLS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…14 This method has been successfully applied to Vis, IR (including MIR and NIR), Raman and Terahertz spectroscopy analysis. Since its algorithm has been described in a large number of articles, 14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] only a brief introduction of the algorithm is presented here for the sake of brevity.…”
Section: Backward Interval Partial Least Squaresmentioning
confidence: 99%
See 2 more Smart Citations
“…14 This method has been successfully applied to Vis, IR (including MIR and NIR), Raman and Terahertz spectroscopy analysis. Since its algorithm has been described in a large number of articles, 14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] only a brief introduction of the algorithm is presented here for the sake of brevity.…”
Section: Backward Interval Partial Least Squaresmentioning
confidence: 99%
“…[14][15][16] Thus, spectral region selection is oen needed in multicomponent spectroscopy analysis in order to build a well-tted model and avoid non-modeled interference. [17][18][19] It has been shown by a lot of researchers 14,[20][21][22][23][24][25][26][27] that spectral region selection could improve the prediction accuracy of the calibration model in spectroscopy analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that wavelength selection is potentially able to improve the prediction ability by finding out an optimized combination of the informative regions. In this work, the optimization of spectral informative regions was accomplished by the iPLS and si-PLS methods [45].…”
Section: Wavelength Selection By Synergy Interval Plsmentioning
confidence: 99%
“…It is noteworthy that the combination of chemometrics and IR spectroscopy is one of the most active spectroscopic elds for the investigation of fuel/petroleum products. 16 Some examples of applications are real-time classication of petroleum products, 17 recognition of gasoline adulteration, 7 classication of source and type of gasoline, 18,19 predicting the long and short residue properties of crude oils, 20 identication of the geographical source of crude oil, 21 determination of the total acid number of crude oil and used gas engine oils, 22,23 identi-cation of motor oil adulteration, 24 and monitoring of diesel fuel quality. 25 In this work, ATR-FTIR assisted by chemometrics was utilized for the discrimination of furnace oil (FO), gas oil (GO) and mazut oil (MO) as three quality grades of fuel oils.…”
Section: Introductionmentioning
confidence: 99%